Assessing the Benefits of Andean Crop Diversity on Farmers' Livelihood: Insights from a Development Programme in Bolivia and Peru. (1st February 2017) - Gotor, Elisabetta; Bellon, Alejandro; Polar, Vivian; Caracciolo, Francesco
Abstract: This paper analyses the impact of a development programme designed at promoting the sustainable use of Andean Grain diversity. Results demonstrate that knowledge‐sharing on agronomic practices, on benefits derived from consumption, and improving Andean Grain quality had a positive impact on income generation and farmer livelihoods. These results demonstrate the effectiveness of programmes aimed at improving rural livelihoods through greater knowledge transfer and use of local agrobiodiversity, wherein private benefits may incentivise the public benefits of agrobiodiversity use and conservation. Findings warrant the need to further monitor and evaluate the potential of agrobiodiversity to improve the well‐being of rural communities. © 2017 The Authors Journal of International Development Published by John Wiley & Sons Ltd.